Expression of IL-17F is associated with non-pathogenic Th17 cells - Wanke, Florian; Kurschus, Florian (Journal of molecular medicine, 2018)
IL-17A and IL-17F share the highest sequence homology of the IL-17 family and signal via the same IL-17RA/RC receptor heterodimer. To better explore the expression of these two cytokines, we used a double reporter mouse strain (IL-17DR mice), where IL-17A expressing cells are marked by enhanced green fluorescent protein (eGFP) while red fluorescence protein (RFP) reports the expression of IL-17F. In steady state, we found that Th17 and γδ T cells only expressed IL-17A, while IL-17F expression was restricted to CD8 T cells (Tc17) and innate lymphoid cells (ILC type 3) of the gut. In experimental autoimmune encephalomyelitis, the vast majority of CNS-infiltrating Th17 cells expressed IL-17A but not IL-17F. In contrast, anti-CD3-induced, TGF-β-driven Th17 cells in the gut expressed both of these IL-17 cytokines. In line with this, in vitro differentiation of Th17 cells in the presence of IL-1β led primarily to IL-17A expressing T cells, while TGF-β induced IL-17F co-expressing Th17 cells. Our results suggest that expression of IL-17F is associated with non-pathogenic T cells, pointing to a differential function of IL-17A versus IL-17F. - KEY MESSAGES: Naïve mice: CD4+ T cells and γδ T cells express IL-17A, and Tc17 cells express IL-17F. Gut ILC3 show differential expression of IL17A and F. Th17 differentiation with TGF-β1 induces IL-17A and F, whereas IL-1β induced cells expressing IL-17A. Th17 cells in EAE in CNS express IL-17A only. Gut Th17 cells induced by anti-CD3 express IL-17A and F together as skin γδ T cells of IMQ-treated mice.